Management of Competency Improvement of Educated Personnel At Vocational High School in Bima City - Salahudddin, Salahuddin (JUPE : Jurnal Pendidikan Mandala, 2025)
The policy of strengthening access at the vocational high school level necessitates the government's readiness to implement educational innovations that align with market demands, ensuring that graduates possess competencies compatible with the needs of the labor market. This study aims to describe the management of enhancing the competencies of educated personnel in vocational high schools in Bima City. Employing a qualitative approach with a case study design, data were collected through interviews, questionnaires, observations, and documentation. Data analysis was conducted using descriptive inductive analysis. The findings reveal that: (1) the graduation rate among students at the four state vocational high schools in Bima City, which served as the research subjects, is notably high, standing at 99.6%, with only 0.4% of students failing to graduate. This elevated graduation rate reflects the students' competency in absorbing knowledge and skills within the school environment. Meanwhile, the absorption rate of graduates into the job market is at 61.54%; (2) the supportive factors for enhancing the competencies of educated personnel include the availability of educational facilities and infrastructure, adequate qualifications of educators, and government support; (3) the program aimed at enhancing the competencies of educated personnel in vocational schools in Bima City encompasses both a departmental skills enhancement program and a partnership program; (4) challenges in improving the competencies of educated personnel at vocational schools in Bima include limited access to training and professional development opportunities, characterized by a notable lack of entrepreneurship training. Furthermore, the school's policies have not yet optimally supported the ongoing development of teachers' competencies, evaluation of practical work has not been maximally conducted collaboratively between schools and industry partners (DUDIKA), and some vocational schools still lack the necessary facilities and infrastructure to meet standards conducive to skill competency and support the development of students' talents and interests. In conclusion, the research indicates that while the percentage of vocational school graduates is exceedingly high, it is along with a sufficiently adequate absorption rate in the job market. This graduation and absorption level synergizes with the support and programs developed by education stakeholders (school community, government, and DUDIKA), despite the presence of unresolved challenges.